Calcareous nannofossils from the Santa Marta Formation (Upper Cretaceous), northern James Ross Island, Antarctic Peninsula. (September 2015) - Guerra, Rodrigo do Monte; Concheyro, Andrea; Lees, Jackie; Fauth, Gerson; de Araujo Carvalho, Marcelo; Cabral Ramos, Renato Rodriguez
Abstract: This study reports on the most stratigraphically extensive nannofloras yet recovered from the Lachman Crags Member of the Santa Marta Formation, James Ross Island, Antarctic Peninsula. The productive samples are dated as early Campanian. These ages are in accord with those provided by ammonites, foraminifera, ostracods and radiolarians from the same locality. The consistent and relatively abundant presence of Gephyrobiscutum diabolum throughout the productive part of the section, a species that has previously only been documented from the Falkland Plateau, extends its geographic distribution to higher latitudes, at least to the Antarctic Peninsula area.